Penerapan Nilai Keagamaan melalui Seni Hadrah Maullatan Al-Habsyi di Kelurahan Pelambuan Kecamatan Banjarmasin Barat - Sari, Rita Purnama Taufiq (Lambung Mangkurat University Indonesia, 2015)
Art Hadrah just listen only and is not applied to them as a message song lyric that contain religious values into everyday life. Neither is the case today in society Pelambuan, as a good religious people of course, we need to understand the application of religious values through art Hadrah, so the application of religious values can be a reference for behavior and community group members hadrah in everyday life. Aims to determine the form of the implementation of arts activities in the community pelambuan hadrah, knowing public participation in the arts hadrah in a song lyric messages, hadrah art knows only as entertainment or as a tradition and know the direct impact that can be felt by people around the hadrah art activities.The method used was a qualitative method. The data source selected by purposive sampling. Data was collected through observation, interviews, and documentation. Analysis of the results of the research is the analysis of the data reduction steps, the data display and verification.The results of the study in the village Pelambuan Western District of Banjarmasin show that (1) the background belakangin founded this group in place so they had nothing with them to form their own initiative and the others follow in their footsteps, a tool used to fly set apart, the number of personnel 12 people, their financial systems by way of savings, well-structured organizational systems, organizational mechanisms from home to home exercise and there is a religious event, da average of these group activities that practice 1 time a week, while for the show to 3 times a week depending on the call. (2) the public participation activities hadrah art goes well enough and every territories also have their peculiarities hadrah grouped respectively. (3) hadrah art not only as a mere entertainment for the community but also as a tradition to release the vows. (4) One of the positive impact will be felt reminded of His greatness and His love to God and His Prophet and its negative impact a lack of public awareness of arts activities hadrah that exist around their territoryBased on these results, the participation of governments, communities and groups can apply the message of the poem t hadrah art into everyday life.Â Keyword: Religious values, hadrah group, community.Â